2014
DOI: 10.1111/jvs.12174
|View full text |Cite
|
Sign up to set email alerts
|

Predicting environmental gradients with fern species composition in Brazilian Amazonia

Abstract: Aim A major problem for conservation in Amazonia is that species distribution maps are inaccurate. Consequently, conservation planning needs to be based on other information sources such as vegetation and soil maps, which are also inaccurate. We propose and test the use of biotic data on a common and relatively easily inventoried group of plants to infer environmental conditions that can be used to improve maps of floristic patterns for plants in general. Location Brazilian Amazonia. Methods We sampled 326 plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 60 publications
8
62
1
1
Order By: Relevance
“…It is likely that if other important soil properties could be included, such as phosphorus and nitrogen concentration or hydrology, the percentage of variation explained by soils would be even higher. This considerably expands the conclusions from earlier studies that have documented soils to be important for plant species turnover at regional extents in Amazonia (Baldeck et al, ; Cámara‐Leret, Tuomisto, Ruokolainen, Balslev, & Munch Kristiansen, ; Higgins et al, ; Pansonato et al, ; Phillips et al, ; Ruokolainen et al, ; Tuomisto, Poulsen, et al, ; Tuomisto, Ruokolainen, Aguilar, et al, ; Tuomisto, Ruokolainen, & Yli‐Halla, ; Zuquim et al, , ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is likely that if other important soil properties could be included, such as phosphorus and nitrogen concentration or hydrology, the percentage of variation explained by soils would be even higher. This considerably expands the conclusions from earlier studies that have documented soils to be important for plant species turnover at regional extents in Amazonia (Baldeck et al, ; Cámara‐Leret, Tuomisto, Ruokolainen, Balslev, & Munch Kristiansen, ; Higgins et al, ; Pansonato et al, ; Phillips et al, ; Ruokolainen et al, ; Tuomisto, Poulsen, et al, ; Tuomisto, Ruokolainen, Aguilar, et al, ; Tuomisto, Ruokolainen, & Yli‐Halla, ; Zuquim et al, , ).…”
Section: Discussionsupporting
confidence: 77%
“…All analyses were carried out using logarithmically transformed values (logCat). This variable was chosen because earlier studies have found its relationship with plant species composition and changes therein to be consistently strong, even when the relationships with the individual cations have varied among regions (Higgins et al, ; Ruokolainen et al, ; Tuomisto et al, ; Tuomisto, Poulsen, et al, ; Zuquim et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…), predicting environmental conditions on the basis of floristic inventories (Sirén, Tuomisto & Navarrete ) and generating better floristic maps for conservation planning (Zuquim et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the herb community may be able to grow taller in soil with higher P content and soil fertility leading to higher herb structural richness. Zuquim et al [49] demonstrated that fern community composition was a good indicator of soil cation concentration. Here, we suggest that herb structural richness may be a good indicator of soil fertility.…”
Section: Structural Richness and Diversitymentioning
confidence: 99%